New mixed salts of l-histidinium(2+) comprising hexafluorosilicate anion - Petrosyan, A.M.; Fleck, M.; Ghazaryan, V.V. (Journal of crystal growth, 2014)
Four mixed salts of amino acid l-histidine comprising hexafluorosilicate anion have been obtained in form of single crystals. These mixed salts are: orthorhombic 2l-His2+∙2ClO4−∙SiF62−∙2H2O (space group P21212, Z=2, a=10.1549(8)Å, b=14.847(1)Å, c=8.7536(7)Å, which is isostructural with recently published 2l-His2+∙2BF4−∙SiF62−∙2H2O), monoclinic 2l-His2+∙2Cl−∙SiF62− (space group C2, Z=2, a=27.037(2)Å, b=6.9849(5)Å, c=5.3630(4)Å, β=91.928(4)°) and isostructural 2l-His2+∙2Br−∙SiF62− (space group C2, Z=2, a=27.063(6)Å, b=7.1013(17)Å, c=5.5076(11)Å, β=92.141(11)°), and triclinic 2l-His2+∙SO42−∙SiF62−∙3H2O (space group P1, Z=1, a=8.5005(17)Å, b=8.7896(18)Å, c=9.7286(19)Å, α=71.49(3)°, β=92.141(11)°, γ=86.17(3)°). •Four mixed salts of l-histidine have been obtained in form of single crystals.•Crystallization conditions, crystal and molecular structures as well as vibrational spectra are discussed.•Both physical properties and anti-caries activity might be employed in applications.